2008
DOI: 10.1007/s00213-008-1387-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose administration prior to a divided attention task improves tracking performance but not word recognition: evidence against differential memory enhancement?

Abstract: Tracking but not memory was enhanced by glucose. This finding suggests that, under certain task conditions, glucose administrations does not preferentially enhance memory performance. One mechanism through which glucose acts as a cognition enhancer is through allowing greater allocation of attentional resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 54 publications
6
59
5
Order By: Relevance
“…However, the hippocampus hypothesis does not account well for previous study findings in which non-memory tasks are improved by glucose (e.g. Donohoe and Benton 1999;Scholey et al 2009). Given that recollection, but not familiarity, is believed to be supported by the hippocampus (Brown and Aggleton 2001;Aggleton and Brown 2006), the ERP results reported here also offer little support for the hippocampus hypothesis, at least in its selectively specific form.…”
contrasting
confidence: 83%
See 1 more Smart Citation
“…However, the hippocampus hypothesis does not account well for previous study findings in which non-memory tasks are improved by glucose (e.g. Donohoe and Benton 1999;Scholey et al 2009). Given that recollection, but not familiarity, is believed to be supported by the hippocampus (Brown and Aggleton 2001;Aggleton and Brown 2006), the ERP results reported here also offer little support for the hippocampus hypothesis, at least in its selectively specific form.…”
contrasting
confidence: 83%
“…By contrast, other studies have found that glucose also improves performance on tasks subserved by other brain regions (e.g. Donohoe and Benton 1999;Martin and Benton 1999;Kennedy and Scholey 2000;Scholey et al 2001;Scholey et al 2009). Studies such as this question the robustness of the 'hippocampus hypothesis'.…”
mentioning
confidence: 57%
“…Glucose ingestion was observed to improve tracking performance, but not recognition memory performance, in the healthy young adult participants. This study demonstrates that oral glucose ingestion can improve performance on non-memory tasks in healthy young adults, possibly by enhancing an individual's capacity to divide attention between two or more concurrent tasks (Scholey et al, 2009a).…”
Section: Divided Attentionmentioning
confidence: 73%
“…In a related study (Scholey et al, 2009a), a dual tasking paradigm was employed in which participants were required to perform an attention task which involved tracking a moving stimulus on a computer screen simultaneously with encoding of a supraspan word list, subsequent to ingestion of glucose or a saccharin placebo. Word list retention was tested by a recognition memory procedure, in which participants were required to distinguish studied words from foils (in the absence of the tracking task).…”
Section: Divided Attentionmentioning
confidence: 99%
“…Benton et al, 1994) can enhance cognitive performance. It also appears that such effects are more marked during cognitive processing involving a relatively high level of mental effort (Kennedy and Scholey, 2000;Scholey et al, 2001Scholey et al, , 2003Scholey et al, , 2008. In addition, studies that have shown improved cognitive performance following the consumption of plant extracts such as Panax ginseng, Ginkgo biloba which may be related to their ability to enhance cerebral blood flow, oxygen utilization or glucose metabolism (Scholey and Kennedy, 2002;Reay et al, 2005Reay et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%